Educational achievement of children with congenital heart disease: Promising results from a survey by the German National Register of Congenital Heart Defects. (January 2019) - Pfitzer, Constanze; Helm, Paul C.; Blickle, Maximilian J.; Rosenthal, Lisa-Maria; Berger, Felix; Abdul-Khaliq, Hashim; Bauer, Ulrike M.M.; Schmitt, Katharina R.L.
Abstract: Background: Survival rates of children with congenital heart disease (CHD) have increased significantly in the decade. There is now increased interest in the long-term outcome and quality of life of these children. Aims: To assess the educational achievement of patients with CHD in Germany. Study design: Cross-sectional study using an online survey. The recruitment of study participants was carried out via the database of the German National Register for Congenital Heart Defects (NRCHD). Subjects: Patients born between 1992 and 2011 were enrolled in the study. For 2609 study participants (female = 1870 (71.7%); 1072 (41.1%) patients; 1537 (58.9%) parents), who participated in the survey, detailed information regarding the underlying CHD diagnosis and clinical data was available. Outcome measures: Age at enrollment, secondary school form, school year repetition, school degree. Results: The large majority of study participants were enrolled at a conventional elementary school (83.4%) and started school at the age of 6 years or below (73.3%). In total 45.7% of graduated study participants graduated with the qualification necessary to study at any university. In terms of analysis of the different CHD severity subgroups 57.3% of patients with a mild CHD, 47.5% with a moderate CHD and only 35.1% suffering from a severe CHD attained a high school diploma. Conclusions: In our study, the majority of participating CHD patients had a standard school career. These initial results are of great importance to affected families and treating physicians as they show that, in general, a normal school career is possible for all CHD patients. Highlights: Survival rates of children with congenital heart disease (CHD) have increased significantly in the decade. There is now an increased interest focusing on the long term outcome and quality of life of these children. In our study, the majority of participating CHD patients had a standard school career. These initial results are of great importance to affected families and treating physicians. In general a normal school career is possible for all CHD patients.